Industrial boilers and heat recovery steam generators : design, applications, and calculations - Ganapathy, V., ....- (Boca Raton : CRC, 2003)
1 Steam and Power Systems 2 Heat Recovery Boilers 3 Steam Generators 4 Emission Control in Boilers and HRSGs 5 Basic Steam Plant Calculations 6 Fuels, Combustion, and Efficiency of Boilers and Heaters 7 Fluid Flow, Valve Sizing, and Pressure Drop Calculations 8 Heat Transfer Equipment Design and Performance 9 Fans, Pumps, and Steam Turbines App. 1 A Quiz on Boilers and HRSGs App. 2: Conversion Factors App. 3: Tables Glossary Bibliography Index
Keywords: Toegepaste warmteleer